Systemically impaired fracture healing in small animal research: A review of fracture repair models. Issue 7 (24th February 2021) - Ryan, Gareth; Magony, Richard; Gortler, Hilary; Godbout, Charles; Schemitsch, Emil H.; Nauth, Aaron
Abstract: Fracture healing is a complex process requiring mechanical stability, an osteoconductive matrix, and osteoinductive and osteogenic biology. This intricate process is easily disrupted by various patient factors such as chronic disease and lifestyle. As the medical complexity and age of patients with fractures continue to increase, the importance of developing relevant experimental models is becoming paramount in preclinical research. The objective of this review is to describe the most common small animal models of systemically impaired fracture healing used in the orthopedic literature including osteoporosis, diabetes mellitus, smoking, alcohol use, obesity, and ageing. This review will provide orthopedic researchers with a summary of current models of systemically impaired fracture healing used in small animals and present an overview of the methods of induction for each condition.